Seabird Bycatch in Alaska Demersal Longline Fishery Trials: a Demographic Summary - Phillips, E. M.; Nevins, H.; Hatch, S.; Ramey, A.; Miller, M.; Harvey, J. (Marine ornithology, 2010)
The seasonal and spatial demographics are summarized for seabirds killed incidentally during gear modification trials for a demersal longline fishery in the Bering Sea. We examined 417 carcasses, including Northern Fulmar Fulmarus glacialis (n = 205), Glaucous-winged Gull Larus glaucescens (n = 103), Short-tailed Shearwater Puffinus tenuirostris (n = 48), Glaucous Gull Larus hyperhoreus (n = 23), Slaty-backed Gull Lams schistisagus (n = 4), Black-legged Kittiwake Rissa tridactyla (n = 1), Laysan Albatross Diomedea immutabilis (n = 1), and unidentified gull species Larus spp. (n = 32). There was a significant male bias in the sex ratio of fulmars but not of gulls or shearwaters. For the top three species killed, the age composition of resident species was dominated numerically by adults (Northern Fulmar--86%; Glaucous-winged Gull--63%), whereas migrant species were primarily immature birds (Short-tailed Shearwater--71%). The majority of migratory Short-tailed Shearwaters (88%) were caught in July and August, whereas 70% of resident fulmars and gulls were caught in October and November. Age-class frequencies did not differ by month of capture, indicating that adult mortality is substantial. Eighty percent of the fulmars caught during July and August were within 200 km of two colonies in the Bering Sea, whereas only 7% of fulmars were caught in the same area during September to November. This is one of the first demographic summaries of seabird bycatch in Alaska longline fisheries. Additional studies of the species, age and sex of seabirds subject to fisheries-related mortality will provide data necessary to evaluate population-level impacts.